(untitled) (International Journal of Engineering and Computer Science, 2018)
Distributed Data mining is a data mining where computation and data is dispersed over multiple independent sites. Service-oriented architecture (SOA) provides integration of many services which coordinate and communicate to one another for their respective goals. Web service based SOAs are used for on-demand computing as well as for developing more interoperable intra or inter organizational systems. Generally data needs be securely protected for privacy purposes in the distributed environment and services provided on time. To serve both the purpose we use Distributed Data Mining (DDM ) integrated on web service Business Process Execution Language (BPEL). Use of local abstraction technique used for privacy purpose